Моделирование реакции на силовое воздействие элемента шейного отдела позвоночника - Веретельник, Олег Викторович (НТУ "ХПИ", 2008)
This work conducts to numerical researches of the cervical spine. Finite element method together with the CAD programs of and experimental information utilized in researches of orthosis. Two charts of research were conducted with orthoses and without him. The analysis of tensions was conducted for intervertebral disks
Keywords: опорно-двигательная система; ортез; геометрическая модель; пациент; затылочные пластины; межпозвоночный диск